THE RELATIONSHIP BETWEEN ATHLETIC IDENTITY AND SPORTS PERFORMANCE AMONG NATIONAL ROWERS DURING DIFFERENT SEASONS OF COMPETITION - Zahra Nili Ahmadabadi; Maesoumeh Shojaei; Afkham Daneshfar (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Aim: Psychologists believe that mental skill like any other skill, can be taught and practiced, and without making use of this factor, it is impossible to achieve peak performance; therefore, elite athletes in different levels and their coaches, shall know about practical concepts and methods of developing mental skills. So, the purpose of this study is to investigate the relationship between athletic identity and sports performance among national rowers during different seasons of competition. Methods: Forty athletes (20 females and 20 males) who were members of the national team with the age mean 23/67 (±3/71) participated in this correlation research. The statistic sample of this investigation was chosen with a special purpose. Athletic identity was measured by Brewer Athletic Identity Questionnaire (AIMS) (1999), and sports performance was measured by 4 physical fitness tests and 4 Proficiency tests in 6 respective stages. The data was analyzed by descriptive statistics, Pearson correlation and Multivariate regression analysis coefficient with P<0.05. Results: The results indicated that there was positive correlation between sports performance and athletic identity during different seasons of competition (P<0.05), but this amount of correlation was different in different seasons of competition. There was significant correlation between athletic identity and sports performance only during the seasons. The results indicated that athletic identity at the end of the training season is a good predictor for athletics success in competition season (P<0.05،f:7/12). So that 48%of athletic performance in competition season can be predicted from athletic identity scales at the end of the training season. Conclusion: Athletic identity increased as sports performance was enhanced; indicating that there was a significant correlation in this season because of its importance for the athletes. Athletes know that if they have good performance, their role of being an athlete or their athletic identity is stabilized.